Review of fire experiments in mass timber compartments: Current understanding, limitations, and research gaps. (18th December 2022) - Mitchell, Harry; Kotsovinos, Panagiotis; Richter, Franz; Thomson, Daniel; Barber, David; Rein, Guillermo
Abstract: The use of mass timber in buildings instead of non‐combustible materials has benefits in sustainability, aesthetics, construction times, and costs. However, the uptake of mass timber in modern construction for medium and high‐rise buildings is currently hindered by uncertainty regarding safety and structural performance in fire. We attribute this to a lack of data. Insufficient understanding means that for building designs beyond the current range of experiments the fire performance is unknown. To address this uncertainty, we review the available data in the scientific literature from 63 compartment fire experiments with timber, the majority of which use cross‐laminated timber (CLT). We found that most experiments reached temperatures 80–180°C greater than in non‐combustible compartments. Timber ceilings have on average a 16% lower char rate than timber walls. The heat release rate contribution of timber has a positive linear relationship with charring rate, however is susceptible to significant uncertainty and variability. There are limits to the data available, particularly in large open‐plan compartments of floor areas larger than 100 m 2 where a wider range of heating conditions occur. Other topics where further understanding is required are compartments with exposed timber areas greater than 75%, compartments with smaller opening areas, and the hazard of smouldering following the flames. Therefore, additional research is needed to design beyond the limits, specifically in compartment size, ventilation, and timber exposure. This paper identifies correlations in the current body of experimental research to improve fire‐safe design of timber buildings.